2007
DOI: 10.1186/1742-2094-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1 (HIF-1) is involved in the regulation of hypoxia-stimulated expression of monocyte chemoattractant protein-1 (MCP-1/CCL2) and MCP-5 (Ccl12) in astrocytes

Abstract: Background: Neuroinflammation has been implicated in various brain pathologies characterized by hypoxia and ischemia. Astroglia play an important role in the initiation and propagation of hypoxia/ischemia-induced inflammation by secreting inflammatory chemokines that attract neutrophils and monocytes into the brain. However, triggers of chemokine up-regulation by hypoxia/ischemia in these cells are poorly understood. Hypoxia-inducible factor-1 (HIF-1) is a dimeric transcriptional factor consisting of HIF-1α an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
121
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 44 publications
13
121
1
3
Order By: Relevance
“…We also found increased protein concentration of CCL12, a proinflammatory chemokine, after hyperoxic reoxygenation, consistent with our recent reports of increased Ccl12 expression in the eye and brain of neonatal mice after hyperoxic reoxygenation (17,26). Mojsilovic-Petrovic et al (27) found increased expression of Ccl12 in astrocyte cultures from P7 mice after hypoxia alone. Hmox1 expression is responsive to both hypoxia and hyperoxia (28), and we found that hyperoxic reoxygenation gave a stronger induction of Hmox1 gene expression than reoxygenation with air.…”
Section: Igf1rsupporting
confidence: 92%
“…We also found increased protein concentration of CCL12, a proinflammatory chemokine, after hyperoxic reoxygenation, consistent with our recent reports of increased Ccl12 expression in the eye and brain of neonatal mice after hyperoxic reoxygenation (17,26). Mojsilovic-Petrovic et al (27) found increased expression of Ccl12 in astrocyte cultures from P7 mice after hypoxia alone. Hmox1 expression is responsive to both hypoxia and hyperoxia (28), and we found that hyperoxic reoxygenation gave a stronger induction of Hmox1 gene expression than reoxygenation with air.…”
Section: Igf1rsupporting
confidence: 92%
“…[33][34][35] Regulation of chemokine expression at the posttranscriptional level involves alterations in mRNA stability. For example, the CXCL1 and CXCL8 mRNA levels increase upon IL-1b stimulation, and the levels remain high up to 8 h in the continued presence of IL-1b, even when coincubated with actinomycin D, an inhibitor of transcription.…”
Section: -24mentioning
confidence: 99%
“…HIF1␣ heterodimerizes with the aryl hydrocarbon receptor nuclear translocator (ARNT, also known as HIF1␤) forming the functional transcription factor HIF1. HIF1 regulates the expression of more than 100 genes, including genes for glycolytic enzymes, sugar transporters, and proangiogenic and inflammatory factors (8,13,18,25). Moreover, HIF1␣ has also been shown to modulate inflammation indirectly by influencing the NF-B signaling pathway (13,20).…”
mentioning
confidence: 99%